Pleural effusion and chylothorax in congenital diaphragmatic hernia - risk factors, management and outcome - Schreiner, Yannick; Sahin, Sidre; Otto, Christiane; Weis, Meike; Hetjens, Svetlana; Zahn, Katrin; Boettcher, Michael; Perez Ortiz, Alba; Rafat, Neysan (Journal of Clinical Medicine, 2024)
Background: Pleural effusion and chylothorax are common complications in the treatment of congenital diaphragmatic hernia (CDH). We set out to identify risk factors for chylothorax development in patients with CDH and to investigate the association of pleural effusion and chylothorax with neonatal morbidity and mortality. Methods: In this retrospective cohort study, we included 396 neonates with CDH treated at our institution between January 2013 and June 2019. Preoperative and postoperative chest radiographs and clinical data were evaluated and correlated with morbidity, complications and mortality. Results: Laboratory-confirmed chylothorax occurred in 58 (18.6%) of all CDH cases. Pleural effusion was frequently observed as a postoperative complication but also occurred as a pre-existing condition. Neonates with large defects of size C and D, patch repair, the need for presurgical and/or postsurgical ECMO support, pulmonary hypertension, liver-up phenomenon and lower relative fetal lung volume were associated with higher occurrences of chylothorax. After stepwise logistic regression, larger CDH defects (p < 0.0001) and the need for postsurgical ECMO (p = 0.0158) remained significant risk factors for CTX to occur (AUC 0.71). The same potential risk factors were used to assess their association with both presurgical and postsurgical pleural effusion. After stepwise logistic regression, only the need for presurgical ECMO remained significantly associated with presurgical PE (p < 0.01, AUC 0.65) and patch repair as the therapeutic intervention remained significantly associated with the occurrence of postsurgical PE (p < 0.0001, AUC 0.80). Patients with CTX had longer durations of both MV (p < 0.0001) and subsequent ventilatory assistance with spontaneous breathing (p = 0.0004), increased total lengths of hospitalization (p < 0.0001), increased durations of ECMO (p < 0.01) and increased incidences of CLD (p < 0.0001) compared to patients without CTX. No significant difference could be found for survival in both groups (p = 0.12). Conclusions: Our data suggest that the incidence of chylothorax is associated with large diaphragmatic defects, the need for postsurgical ECMO and the development of chronic lung disease, but not with survival.
Gesehen am 12.08.2024